roAp STARS AS OBJECTS FOR ASTEROSEISMOLOGY - Dorokhova, T. N.; Dorokhov, N. I. (Одеські астрономічні публікації, 2017)
To date the rapidly oscillating Ap (roAp) stars are one of the best-studied objects of the Main Sequence. There are reviewed the recent results for HD 99563 and γ Equ as examples of stars with stable and unstable oscillations. HD 99563 for its turn compared with the well-studied HR 3831. There are shown how the data obtained in multi-longitudinal phot supplement each other promoting the high specification of the atmospheric and fundamental stellar parameters, of the magnetic fields' geometries and evolutionary state. There are described the difficulties and recent results of roAp stars' searching in the northern hemisphere and, particularly, the data from the Mt. Dushak-Erekdag survey of Odessa Astronomical Observatory.